The Connotations Of The Nominal Structures “Subject And Predicate” Of The Root )Balg( In The Holy Qur’an (Journal of the College of Basic Education, 2024)
This research aims to address the structures of the nominal sentence for caution (report) in the Holy Qur’an and reveal the significance of these structures. It is known that the nominal sentence consists of the predicate and the predicate, taking into account the rank between them, and it precedes the predicate. Because grammarians believe that the predicate is a description in its meaning of the subject; Therefore, it came in proportion to the description in the delay, and since the news came in advance of the subject in all places of the root (balagh); Therefore, the topic will be treated according to the idea of ​​precedence and delay and their significance through the context in which the sentence appears.